Effects of TRPV1 on the hippocampal synaptic plasticity in the epileptic rat brain. Issue 7 (20th May 2015) - Saffarzadeh, Fatemeh; Eslamizade, Mohammad J.; Ghadiri, Tahereh; Modarres Mousavi, Sayed Mostafa; Hadjighassem, Mahmoudreza; Gorji, Ali
ABSTRACT: Temporal lobe epilepsy is often presented by medically intractable recurrent seizures due to dysfunction of temporal lobe structures, mostly the temporomesial structures. The role of transient receptor potential vaniloid 1 (TRPV1) activity on synaptic plasticity of the epileptic brain tissues was investigated. We studied hippocampal TRPV1 protein content and distribution in the hippocampus of epileptic rats. Furthermore, the effects of pharmacologic modulation of TRPV1 receptors on field excitatory postsynaptic potentials have been analyzed after induction of long term potentiation (LTP) in the hippocampal CA1 and CA3 areas after 1 day (acute phase) and 3 months (chronic phase) of pilocarpine‐induced status epilepticus (SE). A higher expression of TRPV1 protein in the hippocampus as well as a higher distribution of this channel in CA1 and CA3 areas in both acute and chronic phases of pilocarpine‐induced SE was observed. Activation of TRPV1 using capsaicin (1 µM) enhanced LTP induction in CA1 region in non‐epileptic rats. Inhibition of TRPV1 by capsazepine (10 µM) did not affect LTP induction in non‐epileptic rats. In acute phase of SE, activation of TRPV1 enhanced LTP in both CA1 and CA3 areas but TRPV1 inhibition did not affect LTP. In chronic phase of SE, application of TRPV1 antagonist enhanced LTP induction in CA1 and CA3 regions but TRPV1 activation had no effect on LTP. These findings indicate that a higher expression of TRPV1 in epileptic conditions is accompanied by a functional impact on the synaptic plasticity in the hippocampus. This suggests TRPV1 as a potential target in treatment of seizure attacks.Synapse 69:375–383, 2015. © 2015 Wiley Periodicals, Inc. Abstract : A higher expression of TRPV1 in the hippocampal CA1 and CA3 areas in epileptic conditions is accompanied by a functional impact on the synaptic plasticity in the hippocampus.